AH-15 The Morphology of Salivary Glands in Water Monitor (Varanus salvator) - Hamny Hamny; Alfajri Saputra; Muhammad Jalaluddin; Sri Wahyuni; Mustafa Sabri (Media Veteriner, 2015)
The Morphology of Salivary Glands in Water Monitor (Varanus salvator)